The Effect of Organic Acids Produced by Phosphate Solubilizing Microbes on Phosphorus Solubilization - Betty Natalie Fitriatin; Nadia Nuraniya Kamaluddin; Diyan Herdiyantoro; Livia Adila (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
The transformation of phosphorus in the soil is facilitated by the activity of the phosphate solubilizing microbes. These microbes have the ability to dissolve fixed P in the soil. The mechanism that plays a role for the phosphorus solubilization is the production of different types of organic acids by phosphate solubilizing microbes. This difference is influenced by two factors, namely the stability constant of organic acid complex compounds with ions, and the structure of the hydroxyl and carboxyl molecules in the main carbon chain. By increasing the organic acids produced by phosphate solubilizing microbes, it will be followed by the formation of organic chelate, so that the bound P becomes dissolved. The reaction that occurs due to the binding process between organic acids and various Al phosphate and Fe phosphate ions The ability of each organic acid to chelate the ion also varies. Each microbe produces different quality and quantity of organic acids. This study aims to determine the relationship between the organic acids secreted by PSM to phosphorus solubilization seen through the best regression modeling that connects between the two variables The relationship between the type and amount of organic acid and phosphorus solubilization still needs to be studied. This study showed that there was a positive correlation between the organic acids produced by phosphate solubilizing microbes (Burkholderia/ Pseudomonas, Bacillus and Aspergillus) and phosphorus solubilization.